Strategi Pengembangan Kawasan Wisata Tanjung Lesung dalam Meningkatkan Ekonomi Masyarakat - Firman Hidayat; Wahyu Widodo; Endayani Endayani (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to analyze the Regional Government's strategy in developing the Tanjung Lesung Tourism Area and identify obstacles and efforts to improve the community's economy. As a Special Economic Zone (SEZ) and a national priority tourism destination, Tanjung Lesung has great potential in encouraging local growth, but its development still faces challenges. The research uses a descriptive qualitative method through interviews, observations, and documentation studies with informants from the Tourism Office, SEZ managers, MSME actors, and Pokdarwis. The analysis refers to the theory of Suryadana's tourism development strategy, including attractions, accessibility, amenities, and institutions. The results of the study show that the government's strategy focuses on the development of attractions through the involvement of MSMEs and cultural preservation, as well as improving facilities with training and community assistance. This strategy has a positive impact on increasing income and job creation. However, there are obstacles in the form of limited regional authority in SEZ management, lack of optimal accessibility and infrastructure, weak collaboration between stakeholders, low capacity of local human resources, and inconsistent promotion. The government's efforts include increasing human resource capacity, facilitating MSMEs in events, and cross-sector coordination. In conclusion, the Tanjung Lesung tourism development strategy has contributed to economic empowerment, but it is not optimal, so stronger synergy is needed between the government, the private sector, and the community to realize sustainable tourism.